Psychosocial Impact of COVID-19 Nursing Home Restrictions on Visitors of Residents With Cognitive Impairment: A Cross-Sectional Study as Part of the Engaging Remotely in Care (ERiC) Project - O'Caoimh, Rónán; O'Donovan, Mark R.; Monahan, Margaret P.; Dalton O'Connor, Caroline; Buckley, Catherine; Kilty, Caroline; Fitzgerald, Serena; Hartigan, Irene; Cornally, Nicola (Frontiers in Psychiatry, 2020)
Background: COVID-19 has disproportionately affected older people. Visiting restrictions introduced since the start of the pandemic in residential care facilities (RCFs) may impact negatively on visitors including close family, friends and guardians. We examined the effects of COVID-19 visiting restrictions on measures of perceived loneliness, well-being and carer quality of life (QoL) amongst visitors of residents with and without cognitive impairment (CI) in Irish RCFs. Methods: We created a cross-sectional online survey. Loneliness was measured with the UCLA brief loneliness scale, psychological well-being with the WHO-5 Well-being Index and carer QoL with the Adult Carer QoL Questionnaire (support for caring subscale). Satisfaction with care (‘increased/same’ and ‘decreased’) was measured. A history of CI was reported by respondents. Sampling was by convenience with the link circulated through university mail lists and targeted social media accounts for two weeks in June 2020. Results: In all, 225 responses were included of which 202 noted whether residents had reported CI. Most of the 202 identified themselves as immediate family (91%) and as female (82%). The majority (67%) were aged between 45-64 years. Most (80%) reported that their resident had CI. Approximately one-third indicated reduced satisfaction (27%) or that restrictions had impaired communication with nursing home staff (38%). Median loneliness scores were 4/9, well-being scores 60/100 and carer QoL scores 10/15. Visitors of those with CI reported significantly lower well-being (p=0.006) but no difference in loneliness (p=0.114) or QoL (p=0.305). Reported CI (p=0.04) remained an independent predictors of lower WHO-5 scores, after adjusting for age, sex, RCF location, and dementia stage (advanced), satisfaction with care (reduced) and perception of staff support measured on the Adult Carer QoL Questionnaire. Conclusion: This survey suggests that many RCF visitors experienced low psychosocial and emotional well-being during the COVID-19 lockdown. Visitors of residents with CI report significantly poorer well-being as measured by the WHO-5 than those without. Additional research is required to understand the importance of disrupted caregiving roles resulting from visiting restrictions on well-being, particularly on visitors of residents with CI and how RCFs and their staff can support visitors to mitigate these.